Dynamic Simulation of Lightning Strikes on Transmission Lines Based on ATP-Matlab - Morales, John A. (2015)
The principal function of an Electric Power System is to supply energy power, maintaining acceptable service conditions. Where, the insulation coordination and protection relays play a crucial role. However, it is clear that lightning strokes on transmission lines can affect the performance of protection devices and insulator strings. In this context, in order to analyze and study the lightning strikes performance, it is necessary to develop simulations of that phenomenon on transmission lines. In this paper a new methodology to develop dynamic simulations of lightning strikes along transmission lines is proposed. The dynamic representation of atmospheric discharges is developed in MATLAB, employing ATP-based files that correspond to the Electric Power System as database for classification schemes. Thereby, the lightning impact point is moved along the transmission line with an interval ΔL until its terminal is reached. For each step ΔL, various simulation cases considering different flash peak current magnitudes, polarities, front times and others characteristics of lightning strikes are developed. Thus, flashes which hit towers, live wires and ground wires are considered. This algorithm can be widely applied to other overhead lines especially for the robustness offered by the interfaces MATLAB-ATP.